Bloodless Gynecological Surgery in Blood Products Refusing Patients: Experience of a Single Institution - Donatella Caserta; Flavia Costanzi; Maria Paola De Marco; Aris Raad Besharat; Christian Napoli; Maria Rosaria Aromatario; Stefano Palomba (Mary Ann Liebert, 2024)
Propose: This pilot study aimed to apply the central tenets of bloodless surgery and to analyze the effectiveness of specific preoperative, intraoperative, and postoperative strategies to minimize the risk for blood transfusion after gynecological surgery in a specific group of patients who refused blood products. Methods: A total of 83 patients undergoing gynecological surgery were included in the study. Forty-two patients received preoperatively oral iron, acid folic, and vitamin B12 supplementation in the 30 days before surgery, and 41 patients did not receive therapy. Results: No significant differences were found when comparing the two study groups. The implementation of all procedures to maintain a bloodless surgery has been helpful, in association with the other available procedures, in achieving optimal management and maintenance of hemoglobin levels, even in the most critical situations. Conclusion: In conclusion, implementing the bloodless approach as much as possible could guarantee the patient better and safer clinical and care management. Furthermore, well-designed research is required to clarify further the effects of bloodless surgery in gynecological patients.